Modern Solutions for the Mechanisms of Taking Medications during Pregnancy - Yashinovna, Tohirova Vasila; Furkatovna, Amanova Madina (American Journal of Bioscience and Clinical Integrity, 2025)
The article is devoted to the issues of pharmacotherapy of pregnant women, taking into account the specific features of drug metabolism in the body of a pregnant woman and the fetus. The issues of complications of drug therapy are highlighted. A list of drugs for the treatment of certain types of somatic pathology in pregnant women is given.